2020
DOI: 10.1111/obr.13138
|View full text |Cite
|
Sign up to set email alerts
|

Weight change from childhood to adulthood and cardiovascular risk factors and outcomes in adulthood: A systematic review of the literature

Abstract: Summary The magnitude of the associations between life‐course change in weight status and health outcomes in adulthood has been inconsistent. This study aims to examine the associations between weight change from childhood to adulthood and cardiovascular disease (CVD) risk factors and outcomes in adulthood. PubMed, Embase and ISI Web of Science between 1 August 1953 and 13 July 2020 were searched, and a total of 52 eligible articles were included. The systematic review supported significant associations betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 102 publications
(268 reference statements)
5
30
0
1
Order By: Relevance
“…Our study found that compared with the persistent non-obese children, those once obese children have a doubled risk of HBP, while the newly developed obesity children tripled the HBP risk of the reference group. Our finding is similar to a recent systematic review about weight change from childhood to adulthood and later life cardiovascular risk factors [37], showing that the related risks reduced when children with obesity turned to be non-obese, and even eliminated when obesity turned to normal weight. But at the same time there are inconsistent studies, for example, Michael's study showed that every single period of obesity could be detrimental to the BP profile no matter the weight status in other periods [36].…”
Section: Different Gob or Aob Status Change With Risk Of Hbpsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study found that compared with the persistent non-obese children, those once obese children have a doubled risk of HBP, while the newly developed obesity children tripled the HBP risk of the reference group. Our finding is similar to a recent systematic review about weight change from childhood to adulthood and later life cardiovascular risk factors [37], showing that the related risks reduced when children with obesity turned to be non-obese, and even eliminated when obesity turned to normal weight. But at the same time there are inconsistent studies, for example, Michael's study showed that every single period of obesity could be detrimental to the BP profile no matter the weight status in other periods [36].…”
Section: Different Gob or Aob Status Change With Risk Of Hbpsupporting
confidence: 91%
“…Along with the epidemic of obesity the prevalence of HBP in children has also increased in recent years, cross-sectional association between obesity and HBP has been well documented, but whether the obesity status change without intervention would have an immediate impact on HBP among children has not been concluded [36][37][38][39]. Our study found that compared with the persistent non-obese children, those once obese children have a doubled risk of HBP, while the newly developed obesity children tripled the HBP risk of the reference group.…”
Section: Different Gob or Aob Status Change With Risk Of Hbpmentioning
confidence: 99%
“…Our data suggest that those children who are overweight or obese might be most vulnerable to the effects of incident or persistent elevated BP on LVMI. As resolving excess weight status is difficult, even in childhood ( 30 ), the high proportion of children able to resolve elevated BP status and the potential benefit to LVMI, as we observed, suggest programs aimed at managing BP among overweight or obese children could be prioritized.…”
Section: Discussionmentioning
confidence: 80%
“…7 Similar findings were showed in one most recent systematic review on weight change from childhood to adulthood and cardiovascular risk factors and outcomes in adulthood. 20 However, findings from the Young Finns Study showed that participants with a BMI trajectory of resolving their overweight/obese weight status from childhood to adulthood had a higher risk of high cIMT in adulthood (although the risk was lower than participants with the trajectory of stable overweight or obesity) compared with participants with stable normal weight. 6 The difference observed between these studies might be due to the different statistical approaches and exposure definitions that were used.…”
Section: Discussionmentioning
confidence: 98%